2004
DOI: 10.1207/s15328023top3101_3
|View full text |Cite
|
Sign up to set email alerts
|

Senior Year Retention of Methods and Statistics Concepts

Abstract: The relationship of high school psychology and natural science courses to performance in a college introductory psychology class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Moreover, our survey results suggest that capstone courses share common pedagogical purposes such as integrating learned material and extending and applying learned material. Previous research suggests that these are important learning goals generally (Scepansky & Carkenord, 2004; Weis, 2004), and our findings suggest that these goals are being addressed through required capstone experiences. With respect to the frequency that capstone courses are offered, our results estimate that psychology major programs at 70.25% of American colleges and universities offer capstone courses and between 47% and 55% require a capstone experience for graduation.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, our survey results suggest that capstone courses share common pedagogical purposes such as integrating learned material and extending and applying learned material. Previous research suggests that these are important learning goals generally (Scepansky & Carkenord, 2004; Weis, 2004), and our findings suggest that these goals are being addressed through required capstone experiences. With respect to the frequency that capstone courses are offered, our results estimate that psychology major programs at 70.25% of American colleges and universities offer capstone courses and between 47% and 55% require a capstone experience for graduation.…”
Section: Discussionsupporting
confidence: 63%
“…It is interesting to note that Scepansky and Carkenord (2004) found a similar pattern of results in which graduating psychology majors retained a surprising proportion of information from their research methods and quantitative methods courses. As a major in psychology, these students are exposed to similar concepts in several courses throughout their studies.…”
Section: Resultsmentioning
confidence: 62%
“…A loftier goal for teachers is that students completing cumulative exams will retain course-related information for a long period of time beyond the end of the semester. Unfortunately, some researchers suggest that students do not retain much content knowledge after completing their introductory courses (Rickard, Rogers, Ellis, & Beidleman, 1988; Spitzer, 1939; VanderStoep, Fagerlin, & Feenstra, 2000; however, see Scepansky & Carkenord, 2004, for dissenting conclusions) and that students experience this decay of knowledge relatively quickly after the semester ends (e.g., in less than 17 days; Bunce, VandenPlas, & Soulis, 2011). However, in the short term, Bunce, VandenPlas, and Soulis (2011) found that cumulative exams were one of several pedagogical techniques that may prevent the decay of student knowledge over the short term (i.e., 17 days).…”
mentioning
confidence: 99%
“…Furthermore, each of these studies supported a different conclusion on which sequence was best. Scepansky and Carkenord (2004) found better student outcomes when students took statistics before research methods courses, Stranahan (1995) found better outcomes when students took statistics and research methods courses concurrently during the same semester, and Stoloff et al (2012) found no difference between different course sequencing. The existing empirical evidence was most limited in evaluating the merits of offering integrated research methods and statistics courses.…”
Section: Discussionmentioning
confidence: 97%
“…When searching SoTL research outside of psychology, we found one additional study conducted by Stranahan (1995) who investigated the impact of different methodological sequences on course grades for nursing and social work students. Similar to Scepansky and Carkenord (2004), Stranahan compared performance for three different sequences: 42 students took statistics before research methods, 126 students took methods before statistics, and 65 students took both courses concurrently during the same semester. Students who took the courses concurrently achieved significantly higher grades in both their statistics and research method classes than students in the other two sequences.…”
Section: Using the Current Sotl Literature To Inform The Debatementioning
confidence: 99%